(untitled) (Педагогіка вищої та середньої школи, 2022)
In the article the author investigates essence of musical aesthetic activity of graduates, music teachers and also the factors increasing it. The pedagogical technology of formation the students’ readiness of to the activisation of the elementary shoolchildren’s art activity is cleared up and experimentally approved. The necessary and sufficient pedagogical conditions of its functioning are defined in the Work of a higher pedagogical school.